Productivity of beet and roquette cultivation as a function of time of establishing intercropping - Cecílio Filho, A. B. [UNESP]; Dos Taveira, S. M C G [UNESP]; Grangeiro, L. C. [UNESP] (My University, 2003)
With the aim of evaluating the effect of intercropping on the productivity of beet and roquette crops, a study was conducted in the Section of Vegetable and Aromatic-Medicinal Plants, FCAV-UNESP, Jaboticabal/SP. The treatments consisted of co-cultivations of roquette (Cultivada) and beets (Early Wonder) established at 0, 7, 14 and 21 days after the transplanting of beets, and as monocultures of beets and roquette. The experiments were delineated in a randomized block design. The productivity of beets in monoculture was not superior to that obtained with intercropping with roquette. The production of dry mass of roquette with intercropping was less than that with monoculture and the reduction was more marked with more delayed establishment of co-cultivation. Intercropping established at 0 and 7 days after the transplanting of beets was the most efficient, with indices of efficient use of land of 1.26 and 1.27, respectively.
Keywords: Beta vulgaris; Cultivation system; Efficient use of land; Eruca sativa